Decadal GPS-derived ice surface velocity along the transect from Zhongshan Station to and around Dome Argus, East Antarctica, 2005–16. Issue 76 (12th March 2018) - Yuande, Yang; Hao, Ke; Zemin, Wang; Fei, Li; Minghu, Ding; Bo, Sun; Bo, Jin; Lianzhong, Wang; Songtao, Ai
ABSTRACT: Using repeat GPS measurements during 2005–16, we calculated and updated two-dimensional high-resolution decadal ice surface velocity estimates along the traverse route from Zhongshan Station to and around Dome Argus, East Antarctica. Along the 71 sites of the transect, the magnitudes of ice velocity increased from near 0 in Dome Argus to 1, 10 and ~100 m a −1 at the sites DT416, DT333 and LT980, respectively. The comparison between GPS and interferometric synthetic aperture radar (InSAR) derived results agree well when the magnitude of the ice surface velocities is faster than 5 m a −1, and disagree for slower flow velocities. A scale value 1.15 and 0.12 can be applied to InSAR derived results over this region with ice surface velocity larger and <5 m a −1, respectively. We attributed the cause of the discrepancy to the insensitivity of InSAR to the magnitude of low ice surface velocities, thus confirming the importance of GPS fieldwork-based ground truth high-resolution ice velocity estimates to constrain ice-sheet dynamics.